Optimalna razporeditev vodnikov daljnovoda glede na emisije elektromagnetnih polj in hrupa - Deželak, Klemen (visokošolska dela, 2011)
The legal procedures to obtain the right of way for the new overhead power lines in Slovenia are extremely difficult nowadays. Due to the large public opposition against the building of the new overhead lines is necessary to invest a lot of effort in both, the planning of overhead power lines and the minimization of their impacts on the environment. In that sense, within the given overhead power line right of way, all of the impacts on the environment should be under prescribed limits. Therefore, most of our attentions should be devoted to minimize emissions of the electromagnetic fields and the audible noise. The aforementioned emissions depend mostly on the values of overhead power line voltage, current and geometrical arrangement of conductors. Especially with the proper arrangement of the overhead power line conductors the emissions of the electromagnetic fields and the audible noise could be essentially reduced. Moreover, with an appropriate software tool, the optimal arrangement of conductors, with respect to the given objective function, could be determined. Such an optimal arrangement of the conductors can be determined with the Differential Evolution based optimization environment proposed in this dissertation. It contains the module for calculating the audible noise emissions as well as the module for calculation the emissions of the electromagnetic fields. In the calculations it is possible to consider the sagged conductors or their approximation with the straight conductors. The aim of this dissertation is to find an optimal arrangement of the three-phase power line conductors. The acceptable emissions of the electromagnetic fields and audible noise are considered as the optimization bounds, while the optimization goal is the minimal height of the tower defined with the attachment of the overhead ground wire. The developed software tool can be used for designing the new overhead power lines, where the restrictions as the width of the overhead power line right of way, the safety clearances, the allowable emission of electromagnetic fields and audible noise are considered. Additionally, the proposed software tool can be applied to check where the overhead power line with the lower rated voltage level can be upgraded to the higher rated voltage level inside already existing right of way.
Keywords: Daljnovodi; Disertacije; elektromagnetno polje; hrup; korona; Optimizacija; poves vodnika; razporeditev vodnikov